Response of Production to Mineral Block Utilization in a Cage-Free System to Mitigate Feather Pecking Behavior in Laying Hen Management - Wijayanti, Desna Ayu; Suripta, Heru; Tey, Donny Kai Hee; Yusuf, Ismail (TERNAK TROPIKA Journal of Tropical Animal Production, 2025)
Feather pecking (FP) is a behavioral issue commonly found in cage-free laying hen systems, particularly in 86-week-old hens, often leading to injuries, stress, and even death. This study aimed to evaluate the effect of mineral blocks as environmental enrichment on reducing FP behavior and improving production performance. A total of 4,800 Isa Brown laying hens were assigned to four treatment groups: P0 (no mineral block), P1 (1 block), P2 (2 blocks), and P3 (3 blocks). Observations included feather pecking frequency, feather condition, mortality and morbidity rates, body weight, and feed consumption. The results showed that the use of mineral blocks significantly reduced FP behavior, with the lowest frequency observed in the P3 group. Mortality and morbidity due to cannibalism were also reduced in groups receiving blocks. Body weight was more stable and tended to increase in enriched groups. The provision of mineral blocks, composed of calcium carbonate, molasses, sodium chloride, mono-sodium phosphate, magnesium oxide, calcium oxide, mineral oil, and sulfur, proved effective in supporting natural pecking behavior and improving poultry welfare. The study concludes that mineral blocks can be a practical strategy to reduce FP and enhance the productivity and welfare of aging laying hens in cage-free systems.